(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
This article talks about the optimization of development, placement and economic efficiency of agro-industrial clusters of enterprises in the current conditions. The authors also share their thoughts on the issues of increasing the profits of agro-industrial clusters in the region.